Benedict XVI a guide for the perplexed - Rowland, Tracey, 1963- (Guides for the perplexed., 2010)
"This guide introduces students of theology to the theoretical axes upon which the theology of Benedict XVI revolves. It begins with a presentation of the key ideas in the works of his intellectual antecedents and contemporary interlocutors and then moves to an account of Benedict's responses to a number of theological crises."--P. [4], cover.